Depresión en la adolescencia en centros de atención primaria: importancia de un problema oculto en salud colectiva - dos Santos Palazzo, L. (Aten Primaria, 2001)
OBJECTIVES: To investigate the prevalence of depression and its relationship to the reason for the consultation and to the medical diagnosis. DESIGN: Descriptive, cross-sectional design. SETTING: Primary care units of a community in Brazil. PATIENTS AND OTHER PARTICIPANTS: Individuals between 13 and 19 years old, who attended 10 primary care units to consult with a non-psychiatric doctor between October 1997 and January 1998 (n = 463). MAIN MEASUREMENTS AND RESULTS: The CETDE (Alonso-Fernández, 1986) was used to measure depression, jointly with a questionnaire for evaluating social and demographic details and data pertinent to the consultation. Prevalence ran at 26.5% (95% CI: 22.6–30.4%). 99.2% cases of depression had not been identified. Complaints were spread over the somatic field (61.1%), or were sex-related (49.5%), mainly pregnancy (31.7%), especially among the cases of depression (p < 0.001). There were few psychiatric-social complaints (1.5%). Diagnoses often coincided with complaints: 59.9% somatic, 38.4% sex-related (pregnancy = 21.6%) and 1.7% psychiatric-social. CONCLUSIONS: Adolescent depression is common in primary care, but is not usually identified. The reason for this may be the kind of depression, which is usually light or focused on just one dimension of human vitality; the doctor´s tendency to centre his/her attention on the complaint without broadening the clinical spectrum; or even because the adolescent expresses his/her emotional problems poorly, which often contributes to the depression not being diagnosed.